BUSTÃN AL-KÃTIBĪN KITAB TATA BAHASA MELAYU PERTAMA KARYA ANAK NEGERI - Moch. Syarif Hidayatullah (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
Research on the influence of Arabic syntax to Malay language orIndonesia language in 19th century is really difficult to be found. In fact, the 19thcentury is the century that is important in the assessment phase of the Indonesiagrammar (Malay), because in this phase began many grammar books anddictionaries of Malay language, both written by Europeans (British-Dutch-French), as Marsden (1812), Crawfurd (1852), Favre (1875), Hollander (1882), andWijk (1889), as well as written by the Malay people Raja Ali Haji (1850 and 1859).There are fundamental differences between the grammar books written by theDutch and the Malays. Books written by Europeans was Europe-centric, whilethe book written by the Malays are very Arab-centric. In fact, since Islam arrivedin the archipelago, the influences of Arabic syntax are felt in the archipelagotexts, especially religious texts. The fact that the Arabic influence is strongenough to precisely the Malay language syntax encourage Ronkel (1899) wrotean article entitled